A disaggregated analysis of change in household out-of-pocket expenditure on healthcare in India, 1995-2004. - Rakesh Chandra,; Aditya Singh,; Saradiya Mukherjee, (Universiti Kebangsaan Malaysia, 2013)
No study has yet attempted to measure mean out-of-pocket expenditure on health care at household level, separately for government and private health facilities in India. Therefore, this study analyses the change in the out-ofpocket expenditure between 1995-96 and 2004 for fifteen major states of India, separately for rural/urban sector and inpatient/outpatient care.